Topical omega-3 fatty acids eyedrops in the treatment of dry eye and ocular surface disease: a systematic review - Paik, Benjamin (2023)
Dry eye is a common inflammatory condition of the ocular surface. While oral omega-3 supplementation for its treatment has been extensively studied, recent large-scale studies have cast doubt on their efficacy. However, efficacy of topical omega-3 has yet to be reviewed. We performed a systematic search of PubMed, Embase, and Cochrane databases for all studies evaluating topical omega-3 in dry eye. Five human and five animal studies were included. Of the five human studies, two were on dry eye disease (DED), one was on contact lens discomfort, and two were on patients undergoing corneal collagen crosslinking. In humans, there is promising evidence for improved ocular surface staining and tear break-up time compared to controls, equivocal evidence for improvements to ocular surface symptoms and meibomian gland dysfunction, and no effect on increasing tear production. Data from animal models largely agree with these findings, and further reveal decreased inflammatory cytokines and monocyte infiltration. Our review suggests that topical omega-3 is a promising treatment for dry eye, but also points to the paucity of evidence in this field. Further trials in humans are required to characterize effects of topical omega-3 and optimize its dosage.